Unlocking work-life balance: the impact of participative leadership on reducing emotional exhaustion - Tauseef Rasheq Ahad; Nasreen Khan; Anusuyah Subbarao; H. M. Mahfuzur Rahman (Cogent Business & Management, 2024)
Amid unprecedented challenges in Malaysia's economy and labour markets, there is a growing inclination among workers to resign in pursuit of a more balanced work-life equilibrium. This shift indicates a changing perspective on employment, where competitive compensation and benefits remain important, but job seekers actively prioritize companies fostering a comprehensive work environment that champions a healthier work-life balance. This study delves into the impact of participative leadership on work-life balance as a means to alleviate emotional fatigue. Employing a quantitative approach and a structured questionnaire distributed through convenience sampling, the research gathered 257 qualified responses from diverse industries. Framed within bounded theory and role theory, the study explores how individuals in Malaysian society manage the interplay between their personal and professional lives to enhance overall well-being. The findings emphasize the substantial role of work interference in personal life, and vice versa, contributing to emotional exhaustion among Malaysian employees. However, the study identifies participative leadership as a crucial mitigating factor against exhaustion. Consequently, fostering empathetic and emotionally intelligent leadership is deemed essential for supporting employees in reducing stress and exhaustion. This research represents a pioneering endeavour in addressing the issue of emotional exhaustion within the distinctive context of work-life balance in Malaysia.
Keywords: 650; Emotional exhaustion; work-life balance; participative leadership